Pengaruh Suhu Awal Air dan Konsentrasi Giberelin (GA3) terhadap Pematahan Dormansi Benih Pepaya California (Carica papaya L.) - Sababalat, Krida Laksana; Wijana, Gede; Darmawati, Ida Ayu Putri (Agrotrop : Journal on Agriculture Science; Vol 14 No 3 (2024), 2024)
The Effect of Water Initial Temperature and Gibberellin Concentration (GA3) on Papaya Seed ( Carica papaya L.) Dormancy Breaking . The increase in papaya fruit production begins with the provision of high-quality seeds, available immediately in sufficient quantities and affordable. Papaya seeds can germinate after undergoing a natural seed dormancy period. Therefore, methods to break seed dormancy are needed leastwise to shorten this dormancy period. This research aims to determine the effect of water initial temperature treatment and gibberellin concentration on breaking papaya seed dormancy. The research was conducted in January - February 2024 at the Plant Breeding and Seed Technology Laboratory, Agroecotechnology Study Program, Faculty of Agriculture, Udayana University. This research used a factorial completely randomized design (CRD) with 2 factors. The first factor is the water’s initial temperature which consists of 4 levels, namely 25°C, 50°C, 60°C, and 70°C. The second factor is the gibberellin concentration consisting of 3 levels, namely 0 ppm, 100 ppm, and 200 ppm. The results showed no interaction between the initial water temperature treatment and the gibberellin concentration on breaking papaya seed dormancy. The initial water temperature did not show a significant effect, whereas the concentration of gibberellin showed a highly significant effect on breaking the dormancy of papaya seeds. A gibberellin concentration of 100 ppm showed the best value for the variable of growth rate (19.35%/etmal), while gibberellin 200 ppm showed the best value for the variables of germination power (81.67%), maximum growth potential (89.33%), growth uniformity (55.50%), and dormancy intensity (10.67%).